Sustainability and Urban Planning Processes. An Integrated Tool for Sustainable Urban Management - Milena Lecca; Giancarlo Deplano (European Regional Science Association (ERSA), 2006)
In the last decades in Italy the debate on the urban planning crisis (Balducci, 1991; Urbani, 2000) had showed a shift from practices informed by politics and negotiation to new positions where planning methods are characterized by a communicative adaptive evaluation of a set of options about land uses and transformations. Within this framework the need emerged of new approaches to planning able to fulfil community expectations. In the light of recent developments in the economic sector and his branches, and primarily in business management, various tools for urban policy making have been recently adopted and implemented in many Italian local authorities: - Implementation of certificated systems for environmental management (Varese Ligure was first Italian municipality to obtain an ISO 14001 certification in 1999); - Use of control and evaluation systems like environmental and strategic plan design aiming at the integration of these practices in a single comprehensive tool, articulated within three phases (organizational, social accounting (18 municipalities have already test these tools and a bill is discussed for their insert in public authorities management); - Employment of participatory practices in the government of environmental problems (Local Agenda 21 processes is hitting an advanced level of implementation both in the municipal and in the provincial level especially in regions like the Emily and Romagna, the Marches, Tuscany, Liguria); - Use of means of communication addressed both to internal members of public authorities and to stakeholders and local community (for example environmental and social statements drawing up by local authorities or sustainability reports like that compiled within 21st Olympic Games organization). However, the analysis of many case-studies showed often the use of these tools it is not directly coordinated with urban planning instruments. In this paper the authors propose a tentative framework for a sustainable decisional and operative) cyclicly. The objective is, as far as these practices are promoted by main international and European agendas and declarations, to connect by this tool local government choices to most important policies on sustainable development.
Keywords: 330